Modelling the conceptual design process with hybridization of TRIZ methodology and systematic design approach - Kamarudin, Khairul Manami; Ridgwaya, Keith; Hassan, Mohd Roshdi (Elsevier, 2015)

(untitled)
The Theory of Inventive Problem Solving (TRIZ) methodology is known to be very effective in complex problem solving. The method, however, needs enhancements in the safety considerations at the earlier stage of conceptual design. This paper presents a hybridized TRIZ methodology with the work of Pahl and Beitz, Systematic Design Approach (SDA) through an effective modelling. This modelling helps in critical problem solving in conceptual design of aircraft parts. The process is applied to a case study of selected aircraft components with a proposal of a systematic and creative methodology in the conceptual designing process. The implications of this study will help aircraft designers to optimize the aircraft parts design in an effective and creative way.